Lev L. Kobylinskij-Éllis: Vom Symbolismus zur ars sacra Eine Studie ueber Leben und Werk - Willich, Heide (Slavistische Beitraege, 1996)
The present work represents the attempt of a scientific-critical study of the life and work of Lev L'vovič Kobylinskij-Éllis (1879-1947) in order to fill a gap in the study of Russian symbolism. The present study should answer the following questions: Is Éllis rightly forgotten? Has he made a contribution to Russian symbolism through his work? Was his work important at the time? Is it of interest today only as a witness of the past or as a personal testimony? Do the works of his second creative period contain important innovations worth examining?